3 days to kill [videorecording (DVD)] - Costner, Kevin; Nielsen, Connie, 1965-; Heard, Amber, 1986-
A dangerous international spy is determined to give up his high stakes life to finally build a closer relationship with his estranged wife and daughter, whom he's previously kept at arm's length to keep out of danger. First, he must complete one last mission, even if it means juggling the two toughest assignments yet: hunting down the world's most ruthless terrorist and looking after his teenage daughter for the first time in ten years while his wife is out of town.